Perilaku Kerja Inovatif Terhadap Kinerja Pemasaran Melalui Customer Relationship Manajemen Sebagai Variabel Intervening pada Bank BNI Wilayah 14 - Ivan Rivai; Arissetyanto Nugroho; Lola Fitriasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the influence of innovative work behavior on marketing performance through Customer Relationship Management (CRM) as an intervening variable. The data analysis methods used in this research are descriptive analysis and quantitative analysis methods. The population in this study consists of 1,217 permanent employees of Bank BNI Region 14. Purposive sampling was chosen as the sampling technique. The sample used in this study consists of 290 respondents, determined using the formula by Krejcie and Morgan (1970). Data was collected through questionnaires distributed via Google Forms to the respondents. The test results show that innovative work behavior has a significant influence on Customer Relationship Management (CRM) with a significance value of 0.000. Additionally, Customer Relationship Management (CRM) significantly affects marketing performance with a significance value of 0.000. Based on the indirect effect test, it is shown that innovative work behavior influences marketing performance through the intervention of Customer Relationship Management (CRM) with a significance value of 0.000.